Analisis Tanggapan Pihak Komersial dan Fiskus terhadap Indikasi Kecurangan pada Pelaporan Pajak Penghasilan - Wahyuni Wahyuni; Mahfiza Mahfiza; Dewi Mahmuda (Al-Buhuts, 2022)
This study aims to analyze the views of commercial parties and the tax authorities in detecting indications of fraud in tax reporting, especially with regard to reporting PPH 23 and PPH Article 4 Paragraph 2. This type of research uses qualitative, this research was conducted at the CV. Citra Panca Mandiri and Account Representative (AR) At KPP Madya Makassar, the informants consisted of 2 CPM staff, namely 1 person from the accounting division, 1 person from the tax division and 2 informants from KPP Madya Makassar, the analytical tool used was a phenomenological approach. Based on the results of data analysis, that in the tax reporting of pph 23 and pph article 4 paragraph 2 there is an indication of fraud if a taxpayer does not report the rights and obligations of tax reporting, it can be seen from the transaction opponent of the CPM withholding tax from cpm income, but the opposite not reporting so that this will make the CPM feel disadvantaged and this is an indication of fraud, and this is supported by the tax authorities who say that this will be followed up or we as a public party will report when the taxpayer's transaction opponent does not report the rights and obligations, as long as there is a report and in our office, and we as a tax party will write and follow up on taxpayers who do not report and pay taxes from the opposing party